2013
DOI: 10.1371/journal.ppat.1003334
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Monovalent Llama-Derived Antibody Fragments (VHH) to Rotavirus VP6 Protect Neonatal Gnotobiotic Piglets against Human Rotavirus-Induced Diarrhea

Abstract: Group A Rotavirus (RVA) is the leading cause of severe diarrhea in children. The aims of the present study were to determine the neutralizing activity of VP6-specific llama-derived single domain nanoantibodies (VHH nanoAbs) against different RVA strains in vitro and to evaluate the ability of G6P[1] VP6-specific llama-derived single domain nanoantibodies (VHH) to protect against human rotavirus in gnotobiotic (Gn) piglets experimentally inoculated with virulent Wa G1P[8] rotavirus. Supplementation of the daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 82 publications
1
48
0
1
Order By: Relevance
“…To support these results, generated VHH molecules directed VP6 in insect cells indicate the same functionality as those expressed in E. coli inducing a broad neutralization activity in vitro and protection against diarrhea and RV shedding in a neonatal mouse model [114]. It has also been shown that the VHH nanoAb can block the infection independently of the RV strain genotypes in vitro and observed a high protection against RV Wa strain in gnotobiotic pigs in vivo [115] as well as VP6-specific IgY Abs from egg yolk [116]. However, DLP2/6 was found to induce neither neutralizing Ab titer nor protecting neonatal Gnotobiotic Piglets against RV challenge [117].…”
Section: The Data Of the Saif/parreno's Groupsmentioning
confidence: 87%
“…To support these results, generated VHH molecules directed VP6 in insect cells indicate the same functionality as those expressed in E. coli inducing a broad neutralization activity in vitro and protection against diarrhea and RV shedding in a neonatal mouse model [114]. It has also been shown that the VHH nanoAb can block the infection independently of the RV strain genotypes in vitro and observed a high protection against RV Wa strain in gnotobiotic pigs in vivo [115] as well as VP6-specific IgY Abs from egg yolk [116]. However, DLP2/6 was found to induce neither neutralizing Ab titer nor protecting neonatal Gnotobiotic Piglets against RV challenge [117].…”
Section: The Data Of the Saif/parreno's Groupsmentioning
confidence: 87%
“…Safe therapeutic approach and passive protection have also been reported following p.o. administration of RV VP6‐VHH nano‐antibodies in neonatal gnotobiotic piglets and mice . These findings demonstrate the potential application of VHH against VP6 to prevent RV‐induced diarrhea and suggest that VHHs should be further investigated as a suitable treatment for gastroenteritis.…”
Section: Mechanisms Of Vp6‐induced Protectionmentioning
confidence: 70%
“…The smaller size of the VHH molecule than conventional antibodies seems to play an important role in this scenario . Furthermore, virus neutralization activity in vitro and in vivo has been reported by insect cells and larvae derived VHH nano‐antibodies to VP6 . Safe therapeutic approach and passive protection have also been reported following p.o.…”
Section: Mechanisms Of Vp6‐induced Protectionmentioning
confidence: 99%
“…4h). VP6 possess broad neutralizing activity in vitro and confer protection against diarrhea in mice (Garaicoechea et al, 2008) and neonatal gnotobiotic piglets (Vega et al, 2013).…”
Section: Ifa Of Pv1 Antigen In Pv1 Infected Vero Cellsmentioning
confidence: 99%